2019
DOI: 10.3390/ijerph16214253
|View full text |Cite
|
Sign up to set email alerts
|

‘Having a Quiet Word’: Yarning with Aboriginal Women in the Pilbara Region of Western Australia about Mental Health and Mental Health Screening during the Perinatal Period

Abstract: Despite high rates of perinatal depression and anxiety, little is known about how Aboriginal women in Australia experience these disorders and the acceptability of current clinical screening tools. In a 2014 study, the Kimberley Mum’s Mood Scale (KMMS) was validated as an acceptable perinatal depression and anxiety screening tool for Aboriginal women in the Kimberley region of Western Australia. In the current study, we explored if it was appropriate to trial and validate the KMMS with Aboriginal women in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…This study also demonstrated that the KMMS was acceptable to women and their health professionals [ 13 ]. The KMMS validation study and subsequent consultations with other groups of Aboriginal women have identified that the inclusion of protective factors is central to Aboriginal women identifying the KMMS as acceptable and culturally safe [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study also demonstrated that the KMMS was acceptable to women and their health professionals [ 13 ]. The KMMS validation study and subsequent consultations with other groups of Aboriginal women have identified that the inclusion of protective factors is central to Aboriginal women identifying the KMMS as acceptable and culturally safe [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cultural translations and adaptations Cultural concerns around standard EPDS suitability are implicit in the decision to translate the EPDS into the Townsville Aboriginal and Islanders Health Services (TAIHS) version (Campbell et al 2008;Hayes et al 2005;Hayes et al 2010) and adapt the EPDS to form the Kimberley Mums Mood Scale (KMMS) (Carlin et al 2019a;Kotz et al 2016;Marley et al 2017). Perinatal Aboriginal women in the Pilbara region in WA supported the KMMS and preferred it over the EPDS because of its simplified language and yarning element of KMMS (Carlin et al 2019a). These modifications and translations address perceived wording and formatting limitations (Kotz et al 2016) and reflect more implicit and common usage of words in the local dialect (Hayes et al 2010) as well as the use of face emoticon in place of a numeric Likert scale.…”
Section: Key Findingsmentioning
confidence: 99%
“…Culturally relevant research methodology Studies describing the process of tool development (TAIHS, KMMS) outlined the importance of being patient, providing time and space to listen to and seek endorsement from Indigenous women with respect to preferences or suggestions for wording, emerging layout themes, and implementation management and strategies (Campbell et al 2008;Hayes et al 2005;Kotz et al 2016;Marley et al 2017). Allowing Indigenous women and communities to have a voice is necessary in building strong partnerships with Indigenous communities (Campbell et al 2008;Carlin et al 2019a;WAPMHU and WNHS 2011). Possible strategies to enhance community engagement and participation is the use of yarning technique (Carlin et al 2019a;Kotz et al 2017) or the use of Indigenous interviewers (Clarke 2008a).…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonisation, forced removal of Aboriginal people from their cultural homelands and their families, and ongoing policies of discrimination have created conditions for increased stress and mental illness within Aboriginal families [11][12][13]. These conditions are often further amplified by limited mental health literacy and/or cultural norms governing the concept of mental illhealth, [14,15] and issues of equity and access to appropriate healthcare providers [16,17] including mental health specialist services [18].…”
Section: Introductionmentioning
confidence: 99%